Pengaruh Pembiasaan Salat Dhuha Sebelum Pembelajaran Terhadap Pembentukan Karakter Religius Siswa MI Muhammadiyah Madureso - Aulia Rachmayanti; Umi Arifah (IAINU Kebumen, 2026)
The purpose of this study was to determine whether or not there was an influence of the habit of performing Dhuha prayer before learning on the formation of the religious character of students at MI Muhammadiyah Madureso. The research method used was a quantitative method, where researchers collected data in the form of numbers, which were then processed to obtain research results. The subjects of this study were 216 students at MI Muhammadiyah Madureso. The instrument used was a questionnaire with a Likert scale. Analysis techniques used were simple regression analysis and t-tests. The results of the study indicate that Dhuha prayer does not have a significant effect on students' religious character. From the regression equation, the value (a) = 19.987, meaning the consistent value of the habit of Dhuha prayer is 19.987. The regression direction coefficient = 0.112 (positive value), meaning that if the habit of Dhuha prayer increases by one (1) unit, then the religious character will increase by 0.112. Meanwhile, based on the results of the t test, it is known that the calculated t value = 1.426 < t table = 1.971. And the significance value of the habit of Dhuha prayer is 0.155 > from 0.05 so that the hypothesis is rejected. Based on the results of the hypothesis test in this study, data was obtained showing that although the regression shows a positive direction, the habit of Dhuha prayer before learning does not have a significant effect on the formation of students' religious character at MI Muhammadiyah Madureso, Kuwarasan, Kebumen.